2019
DOI: 10.3390/su11205672
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Effect of Paddy on Land Surface Temperature in Cold China Based on MODIS Data: A Case Study in Northern Sanjiang Plain

Abstract: Fast-growing crops have been evolved in North China, accompanied by intense paddy expansion, leading to dramatic impacts on the agricultural environment. Among these environmental issues, the impact of paddy expansion on land surface temperature is still unclear. In the present study, based on Landsat images and MODIS land surface temperature (LST) products, the crop pattern and monthly LST in the northern Sanjiang Plain are obtained. A 1 km scale grid unit is built to investigate the relationship between LST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
5
1
Order By: Relevance
“…The correlation coefficient we have found in the different months was stronger as compared to the reported results of Siyal et al [23] and relatively weaker as compared to Guoming et al [19]. Guoming et al [20] reported that the correlation coefficient between paddy rice and LST was stronger (greater than 95%)-except for August, as compared to our study (less than 90%). The reason for this difference in statistical correlation between Guoming's findings and our study is probably due to study area features.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…The correlation coefficient we have found in the different months was stronger as compared to the reported results of Siyal et al [23] and relatively weaker as compared to Guoming et al [19]. Guoming et al [20] reported that the correlation coefficient between paddy rice and LST was stronger (greater than 95%)-except for August, as compared to our study (less than 90%). The reason for this difference in statistical correlation between Guoming's findings and our study is probably due to study area features.…”
Section: Discussioncontrasting
confidence: 87%
“…The logarithmic functional relationship between these two variables has the highest correlation coefficient (R 2 = 0.7318), as compared to the linear relationship (R 2 = 0.7119). Different studies also had similar findings [20,22,23]. It shows that the more vegetative growth on the land, the lower will the LST be, and vice versa.…”
Section: Sowing and Harvesting Dates Identified Through Land Surface ...mentioning
confidence: 58%
See 1 more Smart Citation
“…Li et al, 2020 ;Fu et al, 2016 ;Dong et al, 2015 ). Some studies have also considered the cooling effect of rice field expansion on local surface temperature (T. Liu et al, 2018 ;Huang et al, 2022 ;G. Du et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The heat-mitigation effect of irrigated crop fields has been recognized for a long time (Holmes 1970). In response to ongoing climate changes, an interest has emerged regarding whether and how this effect enhances or mitigates environmental changes (Dong et al 2016;Nocco et al 2019;Du et al 2019;Yang et al 2020). In particular, rice paddies comprise the typical landscapes in many parts of eastern Asia, and their role in heat mitigation may be of interest.…”
Section: Introductionmentioning
confidence: 99%